Post-Impact Characteristics of a Diesel-in-Water Emulsion Droplet on a Flat Surface Below the Leidenfrost Temperature - Faik, Ahmad Muneer El-Deen; Theeb, Maathe Abdulwahed; Zhang, Yang (International Journal of Renewable Energy Development, 2021)
Droplet impingement on solid surfaces takes place in a variety of industrial and environmental applications. However, there are still some areas that are not fully comprehended; emulsion droplet impact on a heated surface is one of these areas that require further comprehension. Hence, the present work represents an experimental exploration for spread characteristics of diesel-in-water (DW) emulsion droplet impacting a heated flat plate. Three different emulsions in which water concentration is set to 10%, 20%, and 30% of the overall emulsion content by volume have been tested in addition to the neat diesel. The temperature of the flat plate is varied over the range 20, 40, 60, and 80ÂºC respectively. Magnified high speed direct imaging and shadowgraphy have been used simultaneously for tracking droplet spread over the heated surface post impact. Droplet spread rate, maximum diameter, rebound height and velocity represent the main evaluated parameters. The results show that the maximum spread diameter is proportional while spread rate is inversely proportional to the increase in plate temperature for all diesel concentrations including the neat diesel. Whereas, droplet rebound height and velocity are found to be more responsive to the variation in diesel concentration than the variation in plate temperature, so they are both minimum in the case of neat diesel and are increasing by the decrease of diesel concentration in the emulsions.